ANALYSIS OF THE INFLUENCE OF STIFFENER TYPE AND MANUFACTURING PROCESS ON MECHANICAL BEHAVIOR OF TITANIUM ALLOY STIFFENED PANEL UNDER AXIAL COMPRESSION - WANG ZhaoHui; MA YuE (Jixie qiangdu)
Stiffened plates is a common structural form in aviation structure. Different types of stiffened plates and different manufacturing processes will affect its mechanical behavior and failure mode. The finite element method is used to establish numerical models of titanium alloy stiffened plates, and to study the effects of the T, L and Z type stiffened plates on buckling mode and failure. The influence of manufacturing processes such as welded, spot welded, riveted and integral panels on buckling and post buckling properties are analyzed. It is shown that the buckling load and the failure load of the T-type stiffened plate are the maximum one. Different manufacturing processes have great influence on the failure load and post-buckling load capacity, among which the post-buckling load capacity of welded stiffened plate is the largest one. At the same time, the most effective stiffening method of 600 mm×600 mm stiffened plate structure is given.